Perceptions of physiotherapists towards the management of non-specific chronic low back pain from a biopsychosocial perspective: A qualitative study - Cowell, I.; O'Sullivan, Peter; O'Sullivan, K.; Poyton, R.; McGregor, A.; Murtagh, G. (2018)
© 2018 Background: Physiotherapists have been urged to embrace a patient-oriented biopsychosocial (BPS) framework for the management of non-specific chronic low back pain (NSCLBP). However, recent evidence suggests that providing broader BPS interventions demonstrates small differences in pain or disability compared to usual care. Little is known about how to integrate a BPS model into physiotherapy practice and the challenges it presents. Objective: To explore the perceptions of physiotherapists' in primary care in England adopting a BPS approach to managing NSCLBP patients. Method: Qualitative semi-structured interviews were conducted with ten physiotherapists working in primary care. A purposive sampling method was employed to seek the broadest perspectives. Thematic analysis was used to analyse the interview transcripts and capture the emergent themes. Results: Three main themes emerged: (1) physiotherapists recognised the multi-dimensional nature of NSCLBP and the need to manage the condition from a BPS perspective, (2) addressing psychological factors was viewed as challenging due to a lack of training and guidance, (3) engaging patients to self-manage their NSCLBP was seen as a key objective. Conclusion: Although employing a BPS approach is recognised by physiotherapists in the management of NSCLBP, this study highlights the problems of implementing evidence based guidelines recommending that psychological factors be addressed but providing limited support for this. It also supports the need to allocate more time to explore these domains in distressed individuals. Engaging patients to self-manage was seen as a key objective, which was not a straightforward process, requiring careful negotiation.